2023
DOI: 10.3390/en16237891
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Single-Cylinder Engine Performance Using Biodiesel Made from Waste Swine Oil

Ramozon Khujamberdiev,
Haeng Muk Cho,
Md. Iqbal Mahmud

Abstract: The global push towards sustainable energy solutions has intensified research into alternative fuels, such as biodiesel. This study investigates the performance and emission characteristics of biodiesel derived from waste swine oil in comparison to traditional diesel fuel. Using an engine running at 75% load across a range of speeds (1200 rpm to 1800 rpm), various metrics such as Brake-Specific Fuel Consumption (BSFC), Brake Thermal Efficiency (BTE), and emissions including Carbon Monoxide (CO), Hydrocarbon (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…As the speed increases, more air is involved in combustion at the same fuel volume, improving the air-fuel mixture quality, allowing the fuel to burn completely and producing more CO2 emissions. Ramozon Khujamberdiev et al [36] also found the same trend in CO2 emissions, which undoubtedly further confirms the accuracy of the experimental results.…”
Section: Carbon Dioxide (Co2)supporting
confidence: 78%
“…As the speed increases, more air is involved in combustion at the same fuel volume, improving the air-fuel mixture quality, allowing the fuel to burn completely and producing more CO2 emissions. Ramozon Khujamberdiev et al [36] also found the same trend in CO2 emissions, which undoubtedly further confirms the accuracy of the experimental results.…”
Section: Carbon Dioxide (Co2)supporting
confidence: 78%
“…A distinguished alternative fuel contender, biodiesel, derived from vegetable, animal, and other waste fats has been extensively used in heavy-duty and marine engines . Reasons are a shortage in supply of fossil fuels, nonedible and waste matter having a great potential to be converted into biodiesel, and in the aspect of environmental protection they have proven to be less polluting and demanding on the environment.…”
Section: Clean Combustion Via Fuel Modification Strategiesmentioning
confidence: 99%
“…46,47 A distinguished alternative fuel contender, biodiesel, derived from vegetable, animal, and other waste fats has been extensively used in heavy-duty and marine engines. 48 Reasons are a shortage in supply of fossil fuels, nonedible and waste matter having a great potential to be converted into biodiesel, and in the aspect of environmental protection they have proven to be less polluting and demanding on the environment. Biodiesels also back up the Renewable Fuel Standard (RFS) program, working toward reducing greenhouse gas emissions and expanding the renewable fuels sector while reducing reliability on fossil fuels.…”
Section: Key Challenges and Development In Biodieselmentioning
confidence: 99%
“…Biodiesel production is an industrial area rising due to the biofuel demand growth and the political and economic issues related to the need to decarbonize the worldwide energy matrix [1,2]. Also known as Fatty Acid Methyl Esters (FAME), it is composed mainly of alkyl esters (saturated and unsaturated) and predominantly produced through transesterification reaction [3][4][5][6][7][8]. In Brazil, the current mandatory biodiesel percentage in diesel is 12% (B12), with projections of a 1% annual increase until 2025 [9].…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, the current mandatory biodiesel percentage in diesel is 12% (B12), with projections of a 1% annual increase until 2025 [9]. However, despite the importance of biodiesel for the Brazilian energy matrix, its application as biofuel in diesel cycle engines is still connected to questions related to the physicochemical properties that can interfere with biodiesel performance, such as a low ester content and low oxidative stability [3,[10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%